The Effects of Long Duration Spaceflight on Sensorimotor Control and Cognition - Tays, Grant D.; Hupfeld, Kathleen E.; McGregor, Heather R.; Salazar, Ana Paula; De Dios, Yiri Eleana; Beltran, Nichole E.; Reuter-Lorenz, Patricia A.; Kofman, Igor S.; Wood, Scott J.; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Seidler, Rachael D. (Frontiers in Neural Circuits, 2021)
Astronauts returning from spaceflight typically show transient declines in mobility and balance. These whole-body postural control behaviors have been investigated thoroughly, while study of the effects of spaceflight on other sensorimotor behaviors is prevalent. Here, we tested the effects of the spaceflight environment of microgravity on various sensorimotor and cognitive tasks during and after missions to the International Space Station (ISS). We obtained mobility (Functional Mobility Test), balance (Sensory Organization Test-5), bimanual coordination (bimanual Purdue Pegboard), cognitive-motor dual-tasking and various cognitive measures (Digit Symbol Substitution Test, Cube Rotation, Card Rotation, Rod and Frame Test) before, during and after 15 astronauts completed 6+ month missions aboard the ISS. We used linear mixed effect models to analyze performance changes due to entering the microgravity environment, behavioral adaptations aboard the ISS and subsequent recovery from microgravity. We identified declines in mobility and balance from pre- to post-flight, suggesting possible disruption and/or downweighting of vestibular inputs; these behaviors recovered to baseline levels within 30 days post-flight. We also identified bimanual coordination declines from pre- to post-flight and recovery to baseline levels within 30 days post-flight. There were no changes in dual-task performance during or following spaceflight. Cube rotation response time significantly improved from pre- to post-flight, suggestive of practice effects. There was a trend for better in-flight cube rotation performance on the ISS when crewmembers had their feet in foot loops on the “floor” throughout the task. This suggests that tactile inputs to the foot sole aided orientation. Overall, these results suggest that sensory reweighting due to the microgravity environment of spaceflight affected sensorimotor performance, while cognitive performance was maintained. A shift from exocentric (gravity) spatial references on Earth towards an egocentric spatial reference may also occur aboard the ISS. Upon return to Earth, microgravity adaptions become maladaptive for certain postural tasks, resulting in transient sensorimotor performance declines that recover within 30 days.